Biomarkers and neuropathology in posterior cortical atrophy: an international, multi‐site study. (20th December 2022) - Chapleau, Marianne; La Joie, Renaud; Mundada, Nidhi S.; Fumagalli, Giorgio G; Formaglio, Maïté; Grinberg, Lea Tenenholz; Hromas, Gabrielle; Kasuga, Kensaku; Lacombe‐Thibault, Mégane; Levin, Netta; Lladó, Albert; Miklitz, Carolin; et al.
Abstract: Background: Posterior cortical atrophy (PCA) is a clinically defined syndrome characterized by impairment in higher‐order visual processing. The underlying pathology in PCA is most commonly Alzheimer's disease (AD), but large‐scale biomarker and neuropathological studies are lacking. In this ongoing project we aim to describe demographic, clinical, biomarker and neuropathological correlates of PCA in a large‐scale international cohort. Method: We contacted 55 research centers conducting PCA research identified in a literature review (n=1353 papers) as well as additional sites recruited through the ISTAART Atypical AD Professional Interest Group (n=7 sites) requesting deidentified, single‐subject data from PCA patients (published and unpublished). Inclusion criteria were: 1. clinical diagnosis of PCA, 2. availability of AD biomarkers (PET or CSF) or 3. availability of autopsy diagnosis. Single‐subject demographic, clinical, fluid, neuroimaging and neuropathological data were collected. Result: As of January 2022, we have collected individual patient data from 390 participants evaluated at 14 sites in 10 countries (Table 1). In the preliminary sample, mean age at symptom onset was 63.1 ± 8.8 years, 62.3% of participants were female, and 78.3% presented with a "PCA‐pure" clinical syndrome by Crutch 2017 diagnostic criteria. APOE4 genotype was present in 45.6% (n=125). Preliminary results show that 82.9% (n=270) display predominant MRI atrophy and 91.9% (n=185) predominant FDG hypometabolism in posterior cortical regions. CSF amyloid markers were positive in 80.2% participants (n=187), while CSF phosphorylated tau markers were positive in 61.4% (n=184). Amyloid PET was positive in 85.2% (n=129) while tau PET was only available in 65 patients (positive in all, and all were amyloid positive). At autopsy (n=36, data from 4 centers), high AD neuropathologic changes were found in all but one patient, who had primary frontotemporal lobar degeneration with TDP‐43 type A pathology. Lewy bodies, argyrophilic grains and cerebral amyloid angiopathy were common co‐pathologies (Figure 1). Conclusion: In a large international cohort, PCA is strongly associated with positive AD biomarkers and neuropathology. Data collection is ongoing, and we further aim to identify clinical features associated with non‐AD underlying causes of PCA.